PERANAN MEDIA KOMUNIKASI WEBLOG BAGI MAHASISWA JURUSAN ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS SAM RATULANGI - Batlayeri, Flora (ACTA DIURNA KOMUNIKASI, 2013)
In this article I want that weblog as communication media takes it’s role towards the learning behavior. It means that weblog as communication media helps students to improve their capacity to read, to write and to get many information in such way that students can achieve good result in learning. Keyword : Weblog, Communication Media, Learning Behaviors